The phenotype masks the genotype: A possible new expression of diabetes - Mimbacas, Adriana; Vitarella, Graciela; Souto, Jorge; Reyes, Ana Laura; Farias, Joaquina; Fernández, Mariana; Fabregat, Matias; Javiel, Gerardo (Journal of Pediatric Genetics, 2012)
The concept of a new form of diabetes, with signs of both types 1 and 2, has not been often considered, until recently. It is of immense interest to explore the role of the admixture that characterizes the Uruguayan population (higher and different from other Latin America countries) for the presence of such expression of that particular disease. We describe here a child who possibly presents with this expression. He had typical signs of both diabetic conditions: type 1 (young age, positive immunologic and genetic markers, ketoacidosis) and type 2 (obesity [body mass index = 36 kg/m2] and acanthosis nigricans). In spite of complying with the established guidelines, therapeutic and nutritional control, quality of life and good metabolic control, the patient's obesity had been continually increasing. Looking for a genetic explanation, we studied three single nucleotide polymorphisms involved in three different metabolic pathways (peroxisome proliferator-activated receptor gamma 2, insulin receptor substrate-1 and uncoupling protein-2) associated with insulin resistance. Our patient showed three mutations, GG, GA, GG, associated with insulin resistance that explains obesity associated with limited response to the commonly used drugs. According to the clinical presentation and the genetic and immunological background, we considered that this patient presents with a new form of diabetes. We have termed this particular disease “hybrid diabetes” because of the involvement of genes associated with both the classical type of diabetes. However, at least in an admixed population such as in Uruguay, clinical classification would not strictly dictate the choice of treatment.
Keywords: Type 1 diabetes; HLA; GAD antibody